Transient Analysis of Grounding Electrodes in Multilayer Soils Using Method of Moments - Colqui, Jaimis Sajid Leon [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2022)
Grounding electrodes are expected to provide a low-impedance path for faults and lightning transient currents and protect the safety of electrical equipment and nearby people against dangerous induced potentials. In this context, a precise model of the grounding electrodes is needed to represent a certain electrode arrangement buried in stratified soil. This paper computes the grounding impedances of different grounding systems buried in three different soil configurations (homogeneous, 2-layer and 3-layer soil) modeled by its frequency-dependent electrical parameters. A simulation model using a commercial full-wave electromagnetic software FEKO to compute the grounding impedances is presented. Method of Moments(MoM), a frequency-domain numerical method, is employed to compute the grounding impedance in a frequency range of100 Hz to 5 MHz. Next, the developed ground potential rise(GPR) generated by two types of lightning currents (first and subsequent return strokes) injected into these grounding systems is computed. Time-domain GPR of each grounding system is also determined using the Vector Fitting (VF) technique combined with the ATP-software. Results show that GPR waveform is reduced when frequency-dependent soils are employed. This reduction is more pronounced in homogeneous and in 2-layersoils of high and moderated resistivity whereas the 3-layer soil has a minor impact due to the lower soil resistivity
Keywords: Computational modeling; Electrodes; Grounding; Method of moments; Software; Soil; Transient analysis